Symbols of Authority in Medieval Islam: History, Religion, and Muslim Legitimacy in the Delhi Sultanate By Blain H. Auer (London and New York: I.B. Tauris, 2012. 237 pages.) (American Journal of Islam and Society, 2013)
This insightful book, useful to scholars and students of Islamic and SouthAsian history, illuminates the place of Islamic thought and institutions in thepolitical regimes of the Delhi Sultanate (1206-1526). Finding late approachesto the historiography of the period unduly focused on “fact” and “fiction,”rather than “meaning,” the author unravels the more complex relationshipbetween history and historiography in six pertinent chapters (p. xix). Theseare complemented by maps, illustrations, thorough endnotes, and a usefulbibliography. As a whole, the cohort of Persian histories read lead to the convincingconclusion that “historians played a major role in producing and sustainingideas about power, justice and Islamic rule of the premodern empire”(p. 160) ...